New Insights into Different Reproductive Effort and Sexual Recruitment Contribution between Two Geographic Zostera marina L. Populations in Temperate China - Xu, Shaochun; Wang, Pengmei; Zhou, Yi; Zhang, Xiaomei; Gu, Ruiting; Liu, Xujia; Liu, Bingjian; Song, Xiaoyue; Xu, Shuai; Yue, Shidong (Frontiers in Plant Science, 2018)
Seagrasses are important components of global coastal ecosystems, and the eelgrass Zostera marina L. is widely distributed along the Atlantic and Pacific coasts in the temperate northern hemisphere, but limited datum related to the contribution of sexual reproduction to population recruitment have been reported. This study aimed to understand eelgrass sexual reproduction and population recruitment in Swan Lake (SLL), and Huiquan Bay (HQB) was included for comparison. Random sampling, permanent quadrats or cores and laboratory seed germination-based experimental methods were employed. The flowering, seed production, seed banks, seed germination, seedling survival, and seedling growth of eelgrass were investigated from July 2014 to December 2015 to evaluate the contribution of sexual reproduction to population recruitment. Results indicated a dominant role of asexual reproduction in HQB, while sexual reproduction played a relatively important role in SLL. The highest flowering shoot density in SLL was 517.27 ± 504.29 shoots m−2 (June) and represented 53.34% of the total shoots at the center site. The potential seed output per reproductive shoot and per unit area in SLL were 103.67 ± 37.95 seeds shoot−1 and 53,623.66 ± 19,628.11 seeds m−2, respectively. The maximum seed bank density in SLL was 552.21 ± 204.94 seeds m−2 (October). Seed germination mainly occurred from the middle of March to the end of May, and the highest seedling density was 296.88 ± 274.27 seedlings m−2 in April. The recruitment from seedlings accounted for 41.36% of the Z. marina population recruitment at the center site, while the sexual recruitment contribution at the patch site (50.52%) was greater than that at the center site. Seeds in SLL were acclimated to spring germination, while in HQB, they were acclimated to autumn germination (early October–late November). Seed bank density in HQB was very low, with a value of 254.35 ± 613.34 seeds m−2 (early October). However, seeds in HQB were significantly larger and heavier than those in SLL (size: P = 0.004; weight: P < 0.001). The recruitment from seedlings accounted for as low as 2.53% of the Z. marina population recruitment in HQB. Our laboratory seed germination experiment, which was conducted in autumn, showed that the seed germination percent in HQB was significantly greater than in SLL at optimal germination temperatures (10 and 15°C; P < 0.001). A laboratory seed germination test at suitable temperature may be a potential novel approach to identify the ecological differences among different geographic populations. It is suggested that the Z. marina population recruitment may have different strategies and adapt to specific local conditions, such as in SLL and HQB, and the temperature regime may control morphological and phonological variations.